Effects of the selective serotonin reuptake inhibitors citalopram and escitalopram on glucolipid metabolism: a systematic review - Yajing Dai; Yajing Dai; Mingzhe Zhao; Mian Li; Mian Li; JinQi Ding; Mengfei Ye; Zhonglin Tan; Sugai Liang (Frontiers in Endocrinology)
ObjectivesType 2 diabetes mellitus (T2DM) and major depressive disorder (MDD) frequently co-occur, highlighting the need to understand the metabolic effects of antidepressants. This systematic review evaluated the impact of citalopram and escitalopram on glucose and lipid metabolism, focusing on glycemic control.MethodsA comprehensive search of PubMed, Embase, Web of Science, PsycINFO, the Cochrane Library and Google Scholar was conducted. Primary outcomes included changes in glycosylated hemoglobin (HbA1c) and fasting blood glucose (FBG). Secondary outcomes assessed lipid profiles (triglycerides, cholesterol, high-density lipoprotein, and low-density lipoprotein) and depressive symptom scales. Subgroup analyses were conducted to evaluate outcomes in patients with comorbid T2DM and MDD and those with MDD only.ResultsThirteen studies involving 502 participants met the inclusion criteria. Six randomized controlled trials, four prospective studies, one cohort trial, one single-arm trial and one three-arm trial. The findings suggest that both citalopram and escitalopram tend to reduce HbA1c and FBG levels. No significant effects on lipid profiles were observed across the included studies.ConclusionCitalopram and escitalopram appear to exert beneficial effects on glycemic control, as evidenced by reductions in HbA1c and FBG. Further high-quality investigations are warranted to validate these findings and guide individualized treatment strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024544963, identifier CRD42024544963.